2012
DOI: 10.1027/1016-9040/a000070
|View full text |Cite
|
Sign up to set email alerts
|

The Unique Contribution of Positive Orientation to Optimal Functioning

Abstract: Literature documents that the judgments people hold about themselves, their life, and their future are important ingredients of their psychological functioning and well-being, and are commonly related to each other. In this paper, results from a large cross-sectional sample (N = 1,331, 48% males) are presented attesting to the hypothesis that evaluations about oneself, one’s life, and one’s future rest on a common mode of viewing experiences named “Positive Orientation.” These results corroborate the utility o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
121
0
11

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 120 publications
(151 citation statements)
references
References 79 publications
12
121
0
11
Order By: Relevance
“…The above results relating psychological variables (personality, coping and perceived stress) to psychopathology are consistent with previous literature (Alessandri, Caprara, & Tisak, 2012;Caprara et al, 2012;Carver & Connor-Smith, 2010;Malouff et al, 2005;Visser et al, 2015). The influence of socio-demographic variables on the development of psychopathology has also been widely studied (Altemus, Sarvaiya, & Epperson, 2014;Tang, Liu, Liu, Xue, & Zhang, 2014).…”
Section: Discussionsupporting
confidence: 80%
“…The above results relating psychological variables (personality, coping and perceived stress) to psychopathology are consistent with previous literature (Alessandri, Caprara, & Tisak, 2012;Caprara et al, 2012;Carver & Connor-Smith, 2010;Malouff et al, 2005;Visser et al, 2015). The influence of socio-demographic variables on the development of psychopathology has also been widely studied (Altemus, Sarvaiya, & Epperson, 2014;Tang, Liu, Liu, Xue, & Zhang, 2014).…”
Section: Discussionsupporting
confidence: 80%
“…Caprara (2009) suggested that PO is such a factor. Caprara defines PO as a general tendency to respond to life experiences with a positive attitude (Alessandri et al 2012;Caprara 2009;Caprara et al 2010). From an empirical point of view, PO is a latent variable that explains the common variability of three variables used most frequently in studies on optimal functioning: self-esteem (measured with Self-Esteem Scale, SES, Rosenberg 1965), life satisfaction (Life Satisfaction Scale, SWLS, Diener et al 1985) and optimism (Life Orientation Test, LOT-R; Scheier et al 1994).…”
Section: Positive Orientationmentioning
confidence: 99%
“…Other fi ndings have shown that positive orientation is a strong predictor of measures related to depression, positive and negative affectivity, quality of friendship, and health. Other fi ndings attest to a positive association of positive orientation with the positive sides of basic personality traits, basic values, psychological well-being, self-effi cacy beliefs, resilience, trust and various indicators of health, pro-sociality and adjustment across domains of functioning, such as family, school, work and civic engagement (Alessandri, Caprara, & Tisak, 2012). Negative associations have been found between positive orientation and depression, shyness, hostile rumination, irritability, violence and somatic complaints.…”
Section: Introductionmentioning
confidence: 98%